EFFECTS OF SOME FERTILIZERS TREATMENTS ON GROWTH OF YOUNG PEACH TREES ( Prunus persica ) CV. DIXIRED FOR BEGINNING OF FRUITING - J. Al-Aaraji (Mesopotamia Journal of Agriculture)
This study was conducted in the pomology field / Horticulture and Landscape Design Dept .during 2008 and 2009 growing seasons to study the response of peach trees cv. Dixired for mineral and organic fertilizers . Compound fertilizer NPK with three ratios of N : P : K ( 1 : 0.5 : 0.5 ) ( 1 : 0.75 : 0.75 ) and ( 1 : 1 : 1 ) for N : P : K respectively ) with three leveles of nitrogen ( 38 , 57 and 76 gm N / tree ) were applied at the middle of February , Meanwhile organic fertilizer ( sheep manure 1.83 % N ) were added at the beginning of January with three levels of nitrogen ( 38 , 57 and 76 gm N / tree ) , and control trees were unfertilizerd . Results indicated that the application of all treatments of mineral and organic fertilizers significantly increased leaves N , P , K , chlorophyll , carbohydrates and dry matter concentration , leaves area , tree height and main stem diameter as compared with control . The best results were obtained with the application of mineral fertilizer at two ratios ( 1 : 1 : 1 and 1 : 0.75 : 0.75 for N : P : K respectively ) at a rate of 76 gm N / tree and organic fertilizer at a rate of 76 gm N / tree .